Assessment of Public Perception and Awareness of the Effect of Poor Solid Waste Disposal on the Environment in Jalingo Metropolis - E.D., Oruonye; Danladi, Tukura Ejati; Y.M., Ahmed (Asian Review of Environmental and Earth Sciences, 2018)
The study assesses the level of public perception and awareness of the effects of poor solid waste disposal on the environment. Data was collected through direct observation and use of questionnaire. The questionnaires were used to obtain the residents perception and awareness of waste generation and disposal methods in the study area. Five political wards (Barade, Majidadi, Sintali A, Turaki A and Turaki B) were purposively selected. The data were analyzed using descriptive statistics. From the study, 39% of the respondents attributed the causes of poor waste disposal to indifferent attitude of the residents, 35% to lack of waste disposal facilities, 22% lack of waste services and 6% to institutional failure. The findings show that most of the wastes generated in the town come from residential households, market places, business shops, government and private offices and municipal areas. Most of the wastes are either disposed off the street or any nearby dumpsite (mostly unapproved and illegal). Most of the respondents claimed to be aware of what constitutes solid waste and effects of poor disposal. However, this claim negates attitude of indiscriminate solid waste disposal in the study area as revealed by the increasing number of open waste dumpsites and wastes that litters most streets of the town. There is need to properly managed the solid waste generated by daily activities of the people. This will help minimize the risk to human health and the environment. Based on the findings the study recommends increase enlightenment campaign through jingles in mass media, recruitment and empowerment of community health workers and sanitary officers and reactivation of the monthly environmental sanitation programme.